Junior High School Students’ Critical Thinking Skills and Concept Mastery on Energy Topic - Yessica Chrisna Dewi; Muhammad Yusup; Apit Fathurohman (Postgraduate, University of Mataram, 2024)
Using quantitative descriptive methods in the form of critical thinking skills tests and concept mastery, this study intends to ascertain the profile of critical thinking skills and concept mastery of junior high school students on energy and its changes. The average score of students on the test was 36.60 out of 100. Students averaged 29.86 on the indication of providing a basic explanation, 29.79 on the indicator of drawing a conclusion, and 28.35 on the indicator of providing a more thorough explanation. Critical thinking abilities are among the things that all three lack. The concept mastery test scores for the cognitive domains of analyzing (C4) and evaluating (C5) were, on average, 35.72 and 34.62, respectively, placing the students in the intermediate range. The findings indicated that due to students' low literacy regarding energy and its changes, their inexperience with working on higher-level thinking questions, and their use of less varied learning methods, their critical thinking skills were in the poor category and their concept mastery was in the moderate category.